The "aerobic base" concept - Richards, R. (1998)
On the much talked about, but misunderstood basis for endurance training - the aerobis base. - What is a swimmer's 'aerobic base'? - How can we measure a swimmer's aerobic base? - Aerobic Base Test for Junior Swimmers (boys under 14 and girls under 13 years). - Aerobic Base Test for Senior Age-Group and Open Swimmers - How Does the Aerobic Base Concept Relate to Other Measures of Performance? - Applying the 'Aerobic Base' Concept to Training